The Effect of Aerobics and Poco-poco Gymnastics to Physical Energy Distribution on Schizophrenia Patients: Effect of Aerobics and Poco-poco Gymnastics to Physical Energy Distribution on Schizophrenia Patients - Enisah Enisah; Gira Lugina; Diah Ernawati; Dian R. Puspita; Evi Rachmawati; Femy Noviantari; Minarti Minarti; Singgih Arfan; Suparji Suparji; Yayah Zakiah (Institute Of Computer Science (IOCS), 2019)
Schizophrenia is the main problem of mental disorder in the world. Most of patients that enter the psychiatric hospital suffer from schizophrenia (85% with schizophrenia). Violent act upon the schizophrenia patients is in line, the rate of nursing diagnose patients who suffer from violent act is the largest number on patient with mental disorder. There are various therapy activities of energy distribution group developed and researched; among them are with gymnastics medium. There are still few review studies on the effects of aerobics gymnastics and poco-poco gymnastics physical energy distribution on schizophrenia patients in reducing the rate of violent act. The objective of the systematic review is to evaluate the effects of aerobics gymnastics and poco-poco gymnastics physical energy distribution on schizophrenia patients in reducing the rate of violent act. Literature searching is conducted on Google Scholar. The study is published in Bahasa Indonesia. There are 578,000 articles found, however only 3 studies fulfill the search criteria. The result of this review shows that the therapy group activity of aerobics gymnastics and poco-poco gymnastics can reduce the rate of violent act. It improves the score of aggression self-control. This intervention can be conducted easily and inexpensively on the institutions providing mental health services.